Wnt signaling regulates chemokine production and cell migration of circulating human monocytes - Natalie Zelikson; Shaina Ben; Michal Caspi; Raneen Tarabe; Yonatan Shaleve; Yael Pri-Paz Basson; Oshrat Tayer-Shifman; Elad Goldberg; Shaye Kivity; Rina Rosin-Arbesfeld (Cell Communication and Signaling, 2024)
Abstract The β-catenin dependent canonical Wnt signaling pathway plays a crucial role in maintaining normal homeostasis. However, when dysregulated, Wnt signaling is closely associated with various pathological conditions, including inflammation and different types of cancer. Here, we show a new connection between the leukocyte inflammatory response and the Wnt signaling pathway. Specifically, we demonstrate that circulating human primary monocytes express distinct Wnt signaling components and are susceptible to stimulation by the classical Wnt ligand—Wnt-3a. Although this stimulation increased the levels of β-catenin protein, the expression of the classical Wnt-target genes was not affected. Intriguingly, treating circulating human monocytes with Wnt-3a induces the secretion of cytokines and chemokines, enhancing monocyte migration. Mechanistically, the enhanced monocyte migration in response to Wnt stimuli is mediated through CCL2, a strong monocyte-chemoattractant. To further explore the physiological relevance of these findings, we conducted ex-vivo experiments using blood samples of patients with rheumatic joint diseases (RJD) – conditions where monocytes are known to be dysfunctional. Wnt-3a generated a unique cytokine expression profile, which was significantly distinct from that observed in monocytes obtained from healthy donors. Thus, our results provide the first evidence that Wnt-3a may serve as a potent stimulator of monocyte-driven immune processes. These findings contribute to our understanding of inflammatory diseases and, more importantly, shed light on the role of a core signaling pathway in the circulation.